Generalizability of Footwear Traction Performance across Flooring and Contaminant Conditions. Issue 2 (3rd April 2018) - Chanda, Arnab; Jones, Taylor G.; Beschorner, Kurt E.
OCCUPATIONAL APPLICATIONS: This study investigates the correlations between available coefficients-of-friction (ACOF) of 17 work shoes across different flooring and contaminant conditions. Five floorings (two vinyl tiles and three quarry tiles) were tested with water, sodium laurel sulfate, and canola oil. Shoe ACOF performance on a single quarry surface with any of the three contaminants was generally applicable to all other quarry-contaminant conditions. Shoe ACOF performance for a vinyl tile was generally applicable to another vinyl flooring for the same contaminant. These findings are anticipated to reduce the need for redundant shoe ACOF testing and clarify the generalizability of traction testing results.